Medication safety with oral antitumour therapeutics in paediatrics (youngAMBORA): A mixed-methods approach towards a tailored care program. - Lensker, Phyllis; Cuba, Lisa; Geßner, Katja; Fromm, Martin; Dörje, Frank; Metzler, Markus (PLoS ONE, 2024)
OBJECTIVE: Oral antitumour therapeutics (OAT) are increasingly used due to improvements in outcomes and their convenient application. However, complex intake regimens pose several challenges. The randomised AMBORA trial (Medication Safety With Oral Antitumour Drugs) demonstrated highly positive outcomes of a clinical pharmacological/pharmaceutical care program for adults treated with numerous OAT, but comparable concepts in paediatrics are lacking so far. METHODS: We used a parallel mixed-methods approach to develop a tailored pharmacological/pharmaceutical care program for OAT in paediatrics (youngAMBORA). We combined a quantitative analysis of tumour entities and used OAT in a paediatric cancer centre with a qualitative survey for patients, caregivers, and healthcare professionals to identify particular demands and educational needs (e.g., application problems, side effects). RESULTS: Leukaemia (77/315) and antimetabolites (95/151) were the most frequently observed entity and OAT, respectively. Of 22 surveyed patients, 81.8% wanted to be involved in oral medication education. Compared to caregivers, significantly more healthcare professionals graded the three most common application problems to be challenging ('Smell/taste': 32/36 vs. 23/42, p = 0.001; 'Refusal of intake': 31/36 vs. 16/42, p<0.001; 'Swallowing problems': 28/36 vs. 21/42, p = 0.011). We identified nine relevant side effects, of which two ('Skin dryness', 'Taste changes') were not included in 15 previously published core side effects of the Common Terminology Criteria of Adverse Events (CTCAE) item library. CONCLUSION: Based on the present findings, the tailored youngAMBORA care program will include: 1) counselling sessions for classic and targeted OAT, 2) child-friendly support with drug application, and 3) systematic evaluation of 17 relevant side effects from patients' and caregivers' points of view including age-appropriate information material.
EVALuna2:583325